A novel antisense long noncoding RNA, TWISTED LEAF, maintains leaf blade flattening by regulating its associated sense R2R3‐MYB gene in rice. Issue 2 (7th February 2018) - Liu, Xue; Li, Dayong; Zhang, Donglei; Yin, Dedong; Zhao, Yi; Ji, Chengjun; Zhao, Xianfeng; Li, Xiaobing; He, Qun; Chen, Runsheng; Hu, Songnian; Zhu, Lihuang
Summary: Natural antisense long noncoding RNAs (lncRNAs) are widespread in many organisms. However, their biological functions remain largely unknown, particularly in plants. We report the identification and characterization of an endogenous lncRNA, TWISTED LEAF ( TL ), which is transcribed from the opposite strand of the R2R3 MYB transcription factor gene locus, OsMYB60, in rice ( Oryza sativa ). TL and OsMYB60 were found to be coexpressed in many different tissues, and the expression level of TL was higher than that of OsMYB60 . Downregulation of TL by RNA interference (RNAi) and overexpression of OsMYB60 resulted in twisted leaf blades in transgenic rice. The expression level of OsMYB60 was significantly increased in TL ‐RNAi transgenic plants. This suggests that TL may play a cis ‐regulatory role on OsMYB60 in leaf morphological development. We also determined that the antisense transcription suppressed the sense gene expression by mediating chromatin modifications. We further discovered that a C2H2 transcription factor, OsZFP7, is an OsMYB60 binding partner and involved in leaf development. Taken together, these findings reveal that the cis ‐natural antisense lncRNA plays a critical role in maintaining leaf blade flattening in rice. Our study uncovers a regulatory mechanism of lncRNA in plant leaf development.